Reactive Oxygen Species Generation by Copper(II) Oxide Nanoparticles Determined by DNA Damage Assays and EPR Spectroscopy - Angelé-Martínez, Carlos (Nanotoxicology, 2017)
Copper(II) oxide nanoparticles ((NP)CuO) have many industrial applications, but are highly cytotoxic because they generate reactive oxygen species (ROS). It is unknown whether the damaging ROS are generated primarily from copper leached from the nanoparticles, or whether the nanoparticle surface plays a significant role. To address this question, we separated nanoparticles from the supernatant containing dissolved copper, and measured their ability to damage plasmid DNA with addition of hydrogen peroxide, ascorbate, or both. While DNA damage from the supernatant (measured using an electrophoresis assay) can be explained solely by dissolved copper ions, damage by the nanoparticles in the presence of ascorbate is an order of magnitude higher than can be explained by dissolved copper and must therefore depend primarily upon the nanoparticle surface. DNA damage is time-dependent, with shorter incubation times resulting in higher EC(50) values. Hydroxyl radical is the main ROS generated by (NP)CuO/hydrogen peroxide as determined by EPR measurements; (NP)CuO/hydrogen peroxide/ascorbate conditions generate ascorbyl, hydroxyl, and superoxide radicals. Thus, (NP)CuO generate ROS through several mechanisms, likely including Fenton-like and Haber-Weiss reactions from the surface or dissolved copper ions. The same radical species were observed when (NP)CuO suspensions were replaced with the supernatant containing leached copper, washed (NP)CuO, or dissolved copper solutions. Overall, (NP)CuO generate significantly more ROS and DNA damage in the presence of ascorbate than can be explained simply from dissolved copper, and the (NP)CuO surface must play a large role.